Undiagnosed placenta percreta complicated by bowel injury and puerperal infection: a case report - Qingge Zhang; Zongyu Liu; Ruimin Zhao; Fei Wu; Limei Fan (BMC Pregnancy and Childbirth)
Abstract Background The refractory obstetric hemorrhage occurring as a result of placenta percreta has been a major cause of maternal mortality. The incidence of placenta accreta spectrum (PAS) disorders has significantly increased recently, with the increasing frequency of cesarean sections and other procedures such as myomectomy, which contribute to uterine scarring. Placenta percreta resulting in uterointestinal injury, however, is far less common. This report describes a case of placenta percreta complicated with bowel injury and delayed puerperal infection. Case A 38-year-old G2P1 female was presented to the hospital 34 days following a normal delivery with symptoms including 10 days of irregular vaginal bleeding and a 1-day history of fever. She had previously undergone surgical treatment for multiple smooth muscle uterine tumors. Ultrasound and magnetic resonance imaging findings suggested myometrial occupancy, prompting speculation of placental percreta. Open exploratory surgery was performed following anti-infection treatment and the correction of anemia. The placenta was found to have penetrated the uterus and caused small bowel erosion. A subtotal hysterectomy and partial small bowel resection were performed, and postoperative pathology confirmed a case of placental percreta. Conclusion Placenta percreta is a rare complication with few testing options available, therefore complicating its diagnosis. Greater awareness of this condition is thus emphasized to minimize the incidence of adverse pregnancy outcomes.